Abolishing War: Criminalizing War, Removing War Causes, Removing War as Institution - Johan Galtung, Erika Degortes, et al (IIUM Press, 2015)
This Book inspired by Tun Mahatir Mohamad and his work on criminalizing war and energizing peace, explores criminalization in Parts I and II, and builsing peace bu removing war causes and removing war as an institution in Parts III and IV